Газодинамические и температурные характеристики теплового аппарата индукционного типа для нагрева воздушного потока - Васецкий, Ю. М.; Кондратенко, И. П.; Жильцов, А. В.; Березюк, А. О. (Energy and Automation, 2017)
UDC 621.1.016.4:621.365.52GASDYNAMIC AND TEMPERATURE CHARACTERISTICS OF INDUCTION TYPE HEAT APPARATUS FOR HEATING AIR FLOWY. Vasetsky, I. Kondratenko, А. Zhiltsov, А. Bereziuk The heat treatment of materials commonly used to intensification of technological processes, provide the required performance properties of the products.Among the variety of thermal plants are particularly important electrothermal installations, allowing to intensify heat transfer processes, to increase the density of energy flow, to reduce plant size and to reduce heat loss. One effective way to improve the heat transfer rate is the use of induction heat input into the metal body, which is particularly important for heating the gas streams.The purpose of research is to develop an analytical mathematical model and analysis of the costs of individual gas flows, their speed and the efficiency of heating the air at the one- and two-way heat transfer in the system of steel pipes heat induction type device intended for heat treatment of grain.The air is heated as it passes along a heated steel tube. Sami pipe heated inductively, for which they are placed inside a fiberglass cylinder, the surface of which is wound coil inductor. The coil is connected to the source of the power frequency voltage.There are two possible organization of the movement of the heated air flow. The first air flows around the heated tube from two sides while moving inside the pipe and in the annulus between the outer surfaces of the outer tube and the surrounding dielectric cylinder. In the second embodiment, the air is passed only through the tubes. In this case, the flow rate at the same rate respectively higher and higher heat flux from the surface of the tubes. However, the air in the annulus to a temperature approaching the temperature of heated tube. Due to the different character of the two heat transfer in the embodiment considered.To investigate the thermal unit of gas dynamic and thermal characteristics necessary to select the original process parameters:- Flow of heated air;- Air temperatures at the inlet pipe and the annulus and the outlet, respectively.Besides the basic input parameters can be set and further, for example, the maximum temperature of the pipes, the allowable temperature of nonmetallic elements, primarily the dielectric cylinder and the flanges when they are made of material with limited allowable temperature.The underlying assumption is the adoption of the one-dimensionality of the processes. It is assumed that the temperature difference between the air tube and heated and, accordingly, the surface heat transfer coefficient does not vary along the length of the thermal unit. It is also believed that the density and specific heat of air have constant values corresponding to the average temperature. Similarly, it is assumed that the parameters associated with the heated pipes have values corresponding to their average temperature. Furthermore, it is assumed that the heat energy is released only at the active site within the length of the inductor, and in this area there is a flow of air heating.All the necessary relations are formulated in the case where the air moves in two streams: the tubes and the annulus. Features inherent in the case of air travel only through the pipes will be considered specifically.The results of specific calculations for certain initial data, characteristic for drying a grain flow of heated air.Conclusions1. The approximate mathematical model of gas flow in straight pipes and heat transfer from the surface of the heated surface during its flow-dimensional turbulent flow, allowed to obtain analytical dependence for basic gas dynamic and thermal characteristics of the heat apparatus for heating air flow, carried out at a flow of their system of steel pipes, the energy input in which it is carried out inductively.2. The use of mathematical models for the two options for the motion of the heated air flow: the one-way heat transfer from the inner surface of pipes during and dual air flows inside tubes and in the annular space, - possible to obtain and analyze cost data of individual gas flows, their speeds , dynamic pressure drop in the system and the efficiency of heating air.3. In the case of two parallel air flow rates of individual gas flows, their velocities, and the maximum outlet air temperature values are different from each other and depend on the number of installed pipes, the equality mentioned parameters for both flows being implemented with different numbers of heat pipes apparatus . The peculiarity of this variant is a slight difference between the maximum temperature in the annulus of the maximum values of the average outlet air temperature, which is essential in selecting the dielectric material of the cylinder.4. It is shown that the apparatus for embodiment of the thermal motion of heated air to only the maximum temperature in the pipes pipes weakly dependent on their number and on the flow of air and heat to the selected unit length ranges. In this embodiment, the heat transfer is difficult with the outside surface of the tube and the dielectric cylinder temperature will approach the temperature of the pipes, which imposes additional requirements on the temperature and the allowable range of pipes of the cylinder material.